Corporate liability through Moot Court in KIAR Practical experience - Hadijah, Ahmad (2023)
The corporate liability provision under Section 17A of the Malaysian Anti-Corruption Commission Act 2009 is designed to ensure that companies are held accountable for any corrupt activities committed by their employees. In the event that a company is found guilty of such offences, they will be fined, their directors and officers will be imprisoned, and other financial penalties will be imposed. Furthermore, the reputation and credibility of the organisation will be adversely affected.